Rainfed agriculture in India: An analysis of performance and implications - SURESH, A; RAJU, S S; CHAUHAN, SONIA; CHAUDHARY, K R (The Indian Journal of Agricultural Sciences, 2014)
The paper examines the trend in the performance of rainfed agriculture in India across major crops during pre- and post-liberalisation period; and ascertains the trend in net income of crop groups of different water requirements in rainfed regions. The major crop groups considered in the analysis are coarse cereals, oilseeds, pulses and cotton. The results indicate that the growth in production of oilseeds and pulses during 1980s and early 1990s weaned out during the subsequent period, probably due to the dilution of some of the policy initiatives like mission mode operation for these crops and adverse terms of trade. However, the yield of most of the crops has increased during the post- liberalisation period. This was also associated with a sharp increase in cost of cultivation. The rate of increase in cost of cultivation was severer for traditional rainfed crops compared to water intensive crops like sugarcane and paddy. Also, the growth in value of production has been lower than the growth in cost of cultivation for the rainfed crops during the post-liberalisation period. The parity of the net income also favoured cultivation of water intensive crops in rainfed lands. Rainfed regions need to focus on yield enhancement through natural resource conservation notably, water; and, incentivise rainfed agriculture through price policies and market opportunities. The study calls for increased investment for rainfed regions for creation of affordable technologies for water conservation and increasing water use efficiency; creation of institutions for better water management and spreading water literacy for sustainable crop production.